Monte Carlo studies of N-methylformamide-dimethyl sulfoxide mixtures - Cordeiro, Joao M. M. [UNESP]; Bosso, Antonio R. S. A. (Elsevier B.V., 2010)
NMF-DMSO mixtures have been used as a model to study the behavior of the peptide bond in non-aqueous medium. Excess enthalpy and the structure of the NMF-DMSO mixture were investigated in the NpT ensemble at 398 K and 1 atm using Monte Carlo simulations. The molecules were kept rigid in the original geometry and the inter-atomic interactions were calculated using the classical Coulomb and 6-12 Lennard-Jones potential. The results for the intermolecular energies between pairs NMF-NMF, DMSO-DMSO. and NMF-DMSO are almost identical. As a consequence the mixture is quasi-ideal with a slightly exothermic excess enthalpy. Analysis of the molecular coordination indicates that quite stable NMF-DMSO supra-species exist in the bulk of the mixture and its structure is strongly orientated by the hydrogen bonds between the NMF and DMSO molecules. The role played by the hydrogen bonds between NMF molecules in the stability of the liquid NMF compares well to the role played by the hydrogen bonds between NMF and DMSO molecules for the stability of the mixture. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Monte Carlo simulations; Peptide bond; Liquid structure; Enthalpy of mixture